Humanities and AI: Ethical Education in Technology Careers - Camargo, Laura Simões; Blay, Enio Alterman; Schmidt, Gabriela Soares (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2024: Anais da XXXIV Brazilian Conference on Intelligent Systems, 2024)
This paper presents a quantitative and qualitative study of the teaching of ethics and related subjects in undergraduate courses in Computing of 17 top-ranked universities evaluated in three different ranking systems. The analysis was performed using documents from the selected universities and semi-structured interviews with professors and a head of department. This article discusses the relevance of ethical and social-oriented teaching and classifies the syllabuses of the sampled disciplines, assessing the type of focus that is apparently given. The overall results show considerable variability in the availability of data, ranging from courses whose content is very detailed to those that don’t present their syllabus at all. Considering that the development of critical reasoning based on ethics is extremely relevant to the education of future Artificial Intelligence developers, the authors concluded that universities are not fulfilling their role adequately.